ANALYSIS OF CAUSES OF DEFECTS AND REPAIR SOLUTIONS ON JERRY CAN PRODUCTS USING ROOT CAUSE ANALYSIS (RCA) AND CAUSE EFFECT DIAGRAMS - Panjaitan, Nismah; Ramadhana, Fauzi; Davin, Christopher (Journal of Industrial Engineering Management, 2024)
PT. ABC is a enterprise engaged inside the manufacturing of price-delivered palm oil based totally merchandise together with ghee and margarine. PT. ABC produces packaging in the form of a jerrycan. In producing jerrycans there are usually faulty products found at the manufacturing ground of PT. ABC. Jerrycan products that do not healthy the characteristics in which elements consisting of materials or materials motive the product to be faulty. If this circumstance maintains, it'll purpose losses for the agency. This examine goals to identify the causes and provide guidelines for best improvement the use of the foundation reason analysis technique and purpose effect diagrams by way of being attentive to components, particularly fabric, human, system and approach. and provide enhancements using the 5W+1H technique and answer tree diagram. based on the root of the trouble discovered, there are three defects, specifically blackspot, broken, and inappropriate colour.